Seasonal water level changes affect plant diversity and littoral widths at different elevation zones in the Erhai Lake - Zhu, Feng; Yuan, Jing; Hou, Zeying; Guo, Xia; Liao, Wanxue; Yang, Shenglin; Chu, Zhaosheng (Frontiers in Plant Science, 2025)
The littoral width of lakeshores is crucial for maintaining and promoting plant diversity. However, it remains unclear how changes in seasonal water level affect littoral widths by regulating plant diversity and soil nutrient content. This study selected three elevation ranges in the lakeshore of Erhai: supralittoral, eulittoral, and infralittoral. We explored the effects of hydrological changes on littoral widths and their potential relationships by analyzing seasonal differences in plant communities and soil physicochemical properties during an extremely drought year. Our results indicated that the most significant seasonal differences in diversity indices, biomass, and soil physicochemical properties were observed in the eulittoral, followed by the infralittoral and supralittoral. The niche breadths of perennials was significantly decreased by 44.4% and the width of the eulittoral was significantly decreased by 48.6% during the winter. Generalized Additive Models (GAMs) were applied to analyze the elevation distribution ranges of dominant species. The results revealed that species with monotonically increasing distributions had the widest niche breadths, followed by symmetric unimodal species, while monotonically decreasing species exhibited the narrowest. Structural equation modeling revealed a positive and significant correlation between flooding days and soil water content and pH, and a negative correlation with plant parameters (species number, biomass, and coverage). Moreover, plant parameters showed a significant positive correlation with plant diversity. Importantly, plant diversity and soil nutrients were significantly positively correlated with littoral widths, suggesting their key roles in influencing littoral widths. This study highlights the significant impact of hydrological seasonal changes on the littoral widths of lakeshore zones, providing valuable guidance for managing wetland water levels in response to extreme drought events.